Legal Protection of Digital Painting Works as Intellectual Property Right - Jessica Calista; Maman Sudirman; Benny Djaja (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
Currently, there is evidence of plagiarism or use of digital painting works that were taken secretly without permission from the owner of the digital painting artwork, because this very free digital space makes intellectual property works vulnerable to theft. The aim and focus of the research is more on analyzing legal protection arrangements for digital painting work. The research method used is normative juridical analysis using legal data in an open source manner with digital painting objects. Based on the research results, the legal protection of digital painting is protected by Law Number 28 of 2014 concerning Copyright and an international agreement in the form of the Trips Agreement. In accordance with Article 4 of the Copyright Law which states that copyright, including digital painting, is an exclusive right which consists of moral rights and economic rights. As for legal remedies for digital painting creators whose creations are misused by other people, they can report them via the E-Commerce Platform and can take legal action outside of court and also take legal action by filing a lawsuit in the commercial court. This research contributes a new regulatory discipline to digital painting.